PENGARUH LATIHAN DUMBELL CURL TERHADAP KEMAMPUAN HASIL SMASH PADA PERMAINAN BOLA VOLI SISWA PUTRA SMAN 1 SAMBELIA LOMBOK TIMUR TAHUN PELAJARAN 2016/2017 - Mahdi Juniarto Ardi; Soemardiawan Soemardiawan; Andi Gilang Permadi (Universitas Pendidikan Mandalika, 2018)
The researcher found a problem experienced by male students of Sambelia 1 STATE High School in volleyball games, namely to the inability of students to smash in this case the ball is not directed, the target is not precise when doing a smash, and a smash has not crossed the net. The expected goal of this study is to find out whether or not there is a dumbbell curl effect on Smash results in volleyball games in male students of SMA Negeri 1 Sambelia Lombok Timur in the school year 2016/2017. This study used the Experimental method with the design of The Static Group Pretest-posttest Design. The population in this study were all volleyball players of SMAN 1 Sambelia which numbered 12 people. Sampling technique uses population studies. while the data analysis method uses statistical analysis with the t-test formula. Based on the results of this study. In accordance with the reality of data analysis, differences in the effect on players given treatment of smash ability use the dumbbell training method. This situation is supported by the t-test analysis that produces t-counts greater than t-table (6.596> 2.201). There is an influence. Is there any effect of dumbbell curl training on the ability of smash results on volleyball games for male students of Sambelia lombok east high school 1 2016/2017 academic year